2022
DOI: 10.1039/d2ma00817c
|View full text |Cite|
|
Sign up to set email alerts
|

An overview on the role of ZnTe as an efficient interface in CdTe thin film solar cells: a review

Abstract: Solar energy may cater current power demand and second generation with modified technologies could play important role. This review presents role of ZnTe as efficient interface to CdTe devices with future road map to improve device performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 199 publications
1
15
0
Order By: Relevance
“…Such thin films can be employed as optical window in CdTe based solar cell devices to augment perfornace together with environment aspects as the prevalent CdS optical window material is a known toxic compound while one needs to ensure required properties in analogy to the champion CdS layer. 8,48 There are some reports in the literature where supramolecular LCs are used in various solar cell devices to acquire higher efficiency. Levitsky et al reported a solar cell based on n-type nanoporous Si (PSi) filled with copper Pc (CuPc).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such thin films can be employed as optical window in CdTe based solar cell devices to augment perfornace together with environment aspects as the prevalent CdS optical window material is a known toxic compound while one needs to ensure required properties in analogy to the champion CdS layer. 8,48 There are some reports in the literature where supramolecular LCs are used in various solar cell devices to acquire higher efficiency. Levitsky et al reported a solar cell based on n-type nanoporous Si (PSi) filled with copper Pc (CuPc).…”
Section: Resultsmentioning
confidence: 99%
“…properties in analogy to the champion CdS layer. 8,48 There are some reports in the literature where supramolecular LCs are used in various solar cell devices to acquire higher efficiency. Levitsky et al reported a solar cell based on n-type nanoporous Si (PSi) filled with copper Pc (CuPc).…”
Section: Xrd Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…20,25,26 PVT collectors based on spectral beam splitting 27 allow the solar cells and the thermal receiver to operate at significantly different temperatures, preventing excessive de-rating of the cells' efficiency while also generating medium to high temperature heat (4100 1C). Furthermore, emerging PV materials (e.g., cadmium telluride (CdTe), perovskites and copper indium gallium diselenide (CIGS)) are now attaining high power conversion efficiencies of up to 23%, 28 and have been demonstrated to work as semi-transparent top-cells in multi-junction configurations. 29 To-date, the implementation of semi-transparent PV solar cells as selective beam splitting filters is limited despite offering a means to efficiently utilise the full solar spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, emerging PV materials ( e.g. , cadmium telluride (CdTe), perovskites and copper indium gallium diselenide (CIGS)) are now attaining high power conversion efficiencies of up to 23%, 28 and have been demonstrated to work as semi-transparent top-cells in multi-junction configurations. 29 To-date, the implementation of semi-transparent PV solar cells as selective beam splitting filters is limited despite offering a means to efficiently utilise the full solar spectrum.…”
Section: Introductionmentioning
confidence: 99%